THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT ADINDA PERMATA MULIA - Muhammad Ramdhan; Rahayu, Suharni (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of leadership style on employee performance of PT Adinda Permata Mulia. The research method used in this research is descriptive with a quantitative approach. The sampling technique using saturated samples so that the number of samples in this study was 41 respondents. Data analysis techniques using simple linear regression. The results showed that there was a positive and significant influence of leadership style variables on the performance of PT Adinda Permata Mulia employees. This is evidenced by the value of tcount> ttable, namely 7.834> 2.023 with a probability value (significance) = 0.000, which is below 0.05.